Tendencies in the European and Hungarian Management Consulting Market - Tokár-Szadai, Ágnes (Theory, Methodology, Practice – Review of Business and Management, 2012)
There are two main approaches in the relevant literature of consulting: the first approach emphasises that consultants are helpers; they help clients with solving their problems. The second approach, which views consulting as a special professional service, is used by professional associations and institutes of management consultants. I would like to summarise the different approaches and definitions of management consulting in the relevant English and German literature, evaluate the development of the definitions, and integrate the different approaches. After delineation of the complex definition of management consulting, I will summarise tendencies in the European and Hungarian management consulting market based on surveys of the European Federation of Management Consultancies Associations (FEACO) in the period 1998-2011.